Livestock as a source of greenhouse gas emission - Vazquez-Carrillo, Maria Fernanda; Robles-Jimenez, Lizbeth Esmeralda; Radic Schilling, Sergio Javier; Castelan-Ortega, Octavio Alonso; Gonzalez-Ronquillo, Manuel (My University, 2024)
In this chapter, we will focus on describing enteric methane (CH4) as an energy loss and its role as a greenhouse gas (GHG), used strategies to reduce enteric CH4 in ruminants, and the most current techniques used to quantify enteric CH4 emissions in ruminants. The importance of studying animal bioenergetics to explains its apparent fragmentation and dissociation along its pathway in cattle. Cattle maintain a close symbiosis with their rumen microbiota, which provide them with the necessary energy resulting from the fermentation of the food they ingest. However, this process is not 100% efficient. Enteric CH4 is an energy loss and a GHG that contributes to global warming. Likewise, it is described how the manipulation of ruminal fermentation is one of the main CH4 mitigation strategies. Currently, the use of additives rich in secondary metabolites, such as tannins, saponins, flavonoids, and essential oils (EOs), among others, has been studied. Finally, techniques currently used to measure enteric CH4 emissions include sulfur hexafluoride (SF6) and an automated head camera system (GreenFeed) that can monitor CH4 and carbon dioxide (CO2) mass fluxes from ruminant respiration and burping.
Keywords: enteric methane; handheld laser methane detector; mitigation; sulfur hexafluoride